Evaluation of zonulin levels in patients with migraine - Gözde Ülfer; Burcu Polat; Ahmet Yabalak; Çağrı Çakıcı (BMC Neurology)
Abstract Background Zonulin regulates permeability in blood–brain and intestinal barriers. The pathophysiology of migraine is based on the effect of neurogenic inflammation. The aim of the current investigation was to examine the serum zonulin level in individuals suffering from migraine. Methods The sample comprised 40 individuals who had migraine and 40 controls. Disease duration, attack duration, attack frequency, Visual Analog Scale (VAS) scores, and comorbidities were available for the migraine group. Serum zonulin levels were evaluated by using the ELISA method. Results There were no statistically significant differences between the two groups concerning age or gender (p > 0.05). The zonulin value of patients with migraine was higher when compared to the controls, indicating a significant difference (p = 0.037; p < 0.05). The zonulin level did not correlate with disease duration, attack duration, VAS score, or attack frequency (p > 0.05). The receiver operating characteristic curve analysis of zonulin revealed a cut-off value of 30.58 and above, at which it had 52.50% sensitivity, 77.5% specificity, 70% positive predictive value, and 62% a negative predictive value. The area under the curve was 63.6%, and the standard error value was 6.3%. The analysis also showed a statistically significant correlation between migraine diagnosis and a zonulin level of 30.58 (p = 0.006; p < 0.01). Conclusions Elevated zonulin levels in patients with migraine support the disruption of the intestinal barrier and neuroinflammation in these patients. The zonulin level may be a predictive biomarker of migraine. Multicenter, randomized trials are needed to evaluate treatments for intestinal permeability and zonulin levels in migraine patients.